Cancer-associated fibroblasts and their role in tumor progression - M. S. Ermakov; A. A. Nushtaeva; V. A. Richter; O. A. Koval (Вавиловский журнал генетики и селекции, 2022)
The stromal elements of a malignant tumor can promote cancer progression and metastasis. The structure of the tumor stroma includes connective tissue elements, blood vessels, nerves, and extracellular matrix (ECM). Some of the cellular elements of the tumor stroma are cancer-associated fibroblasts (CAFs). The origin and function of CAFs have been actively studied over the past thirty years. CAFs produce collagen, the main scaffold protein of the extracellular matrix. Collagen in the tumor stroma stimulates fibrosis, enhances the rigidity of tumor tissue, and disrupts the transmission of proliferation and differentiation signaling pathways. CAFs control tumor angiogenesis, cell motility, tumor immunogenic properties, and the development of resistance to chemo- and immunotherapy. As a result of metabolic adaptation of rapidly growing tumor tissue to the nutrients and oxygen deprivation, the main type of energy production in cells changes from oxidative phosphorylation to anaerobic glycolysis. These changes lead to sequential molecular alterations, including the induction of specified transcriptional factors that result in the CAFs activation. The molecular phenotype of activated CAFs is similar to fibroblasts activated during inflammation. In activated CAFs, alpha-smooth muscle actin (α-SMA) is synthetized de novo and various proteases and fibronectin are produced. Since CAFs are found in all types of carcinomas, these cells are potential targets for the development of new approaches for anticancer therapy. Some CAFs originate from resident fibroblasts of the organs invaded by the tumor, while others originate from epithelial tumor cells, which are undergoing an epithelial-mesenchymal transition (EMT). To date, many molecular and metabolic inducers of the EMT have been discovered including the transforming growth factor-beta (TGF-β), hypoxia, and inflammation. This review classifies modern concepts of molecular markers of CAFs, their functional features, and discusses the stages of epithelial-mesenchymal transition, and the potential of CAFs as a target for antitumor therapy.